Counterparty Risk: Implications for Network Linkages and Asset Prices. (22nd July 2022) - Grigoris, Fotis; Hu, Yunzhi; Segal, Gill
Abstract: We study the relation between trade credit, asset prices, and production-network linkages. Empirically, firms extending more trade credit earn 7.6$%$ p.a. lower risk premiums and maintain longer relationships with customers. Using a production-based model, we quantitatively explain these novel facts. Trade credit reduces the departure probability of high-quality customers, thereby reducing firms' exposures to systematic costs incurred in finding new customers. The mechanism predicts that the aggregate amount of trade credit proxies for customer-search costs and that suppliers with shorter-duration links to customers command higher expected returns. We confirm these and other novel predictions in the data.